The combined use of embryos and semen for cryogenic conservation of mammalian livestock genetic resources - Boettcher, Paul J (BioMed Central, 2005)
The objective of this empirical simulation study was to evaluate the use of a combination of semen and embryos in the creation of gene banks for reconstruction of an extinct breed. Such an approach was compared for banks with varying proportions of embryos on the basis of the amount of the material to be stored, time for reconstruction, maintenance of genetic variability, and probability of failure during reconstruction. Four types of populations were simulated, based on reproductive rate: single offspring, twinning, enhanced reproduction, and litter bearing. Reconstruction was simulated for banks consisting of different combinations of semen and reduced numbers of embryos (expressed as a percentage of the material needed for a bank containing exclusively embryos and ranging from 10 to 90%). The use of a combination of semen and embryos increased the number of insemination cycles needed for reconstruction and the level of genetic relatedness in the reconstructed population. The risk for extinction was unacceptably high when a very low proportion of embryos (< 20%) was used. However, combining semen with embryos could decrease costs, allowing for the conservation of more breeds, and specific strategies for semen use could decrease the level of relationships in the reconstructed breed.